PP.07.28: COMPARISON OF 12-WEEKS' ANTIHYPERTENSIVE EFFECT OF FIMASARTAN 60 MG OR 120 MG A DAY IN COMPARISON WITH CANDESARTAN 8 MG A DAY IN THE PATIENTS WITH MILD TO MODERATE HYPERTENSION. (June 2015) - Chae, S.; Lee, J.; Yang, D.; Hwang, J.; Hur, S.; Cha, T.; Kim, K.; Kim, M.; Chun, K.; Hong, G.; Lee, S.; Kim, D.; et al.
Abstract : Objective: Fimasartan is a new antihypertensive drug which blocks AT-1 receptor selectively. It exhibited a potent antihypertensive effect and quick onset of the effect. We investigated antihypertensive effect of 60 and 120 mg of Fimasartan and its safety in comparison with 8 mg of Candesartan. Design and method: After 2 weeks' placebo run-in period, 290 patients with mild to moderate hypertension (diastolic blood pressure (DBP), 90 ∼ 110 mmHg) aged from 19 to 75 years old were randomly assigned to 60 mg, 120 mg daily of Fimasartan or 8 mg daily of Candesartan. They were administered for 12 weeks without dosage adjustment. Primary endpoint was difference in changes of DBP from baseline at 12 weeks. Results: After 12 weeks' treatment, DBP and systolic blood pressure (SBP) were decreased significantly in all 3 groups. The decrease of DBP at 12 weeks was larger, but not statistically significant, in Fimasartan 60 mg compared with the Candesartan 8 mg group with the difference of 1.72 ± 8.32 mmHg (95% confidence interval, -0.71∼ 4.15 mmHg, p = 0.16). Lower margin of the confidence interval, -0.71 mmHg, exceeded the pre-defined non-inferiority margin, -3.0 mmHg. DBP lowering effect of Fimasartan 120 mg was also non-significantly larger than the candesartan 8 mg (difference, 1.58 ± 8.27 mmHg, p = 0.20). The decrease of SBP was also non-significantly larger in Fimasartan 60 mg compared with the candesartan 8 mg group (difference, 3.50 ± 12.63 mmHg, p = 0.06). However, SBP lowering effect of the Fimasartan 120 mg was statistically larger than the candesartan 8 mg (difference 4.98 ± 13.99 mmHg, p = 0.02). Responder rate (DBP < 90 mmHg or DBP lowering > 10 mmHg at 12 weeks) was also non-significantly greater in both Fimasartan groups (Fimsartan 60 mg, 81%; Fimasartan 120 mg, 72%; Candesartan 8 mg, 71%). Safety profile of the Fimasartan 60 mg and 120 mg was similar to candesartan 8 mg, with slightly higher, but statistically not significant, incidence of hepatic enzyme elevation in Fimasartan 120 mg. Conclusions: Fimasartan, a newly available AT-1 receptor blocker, is an effective antihypertensive agent, comparable to candesartan, with good safety profile.